Personality Traits and Self-Efficacy Learning Performance: Analysis of Students Carrying Out Practical Courses (Universitas Negeri Semarang, 2021)
Mata kuliah praktikum memiliki tantangan yang berbeda dengan mata kuliah teori. Banyak faktor yang berhubungan dengan efikasi diri mahasiswa ketika mengikuti mata kuliah praktik. Penelitian ini dilatarbelakangi oleh fenomena mahasiswa yang mengalami kesulitan dalam mengikuti mata kuliah praktikum konseling. Fokus dari penelitian ini adalah untuk memprediksi efikasi diri berdasarkan tipe kepribadian. Ten Items Personality Inventory (TIPI) dan Self-Efficacy Learning Performance (SELP) diberikan kepada 103 mahasiswa dan dianalisis dengan menggunakan korelasi product moment. Hasil penelitian menunjukkan bahwa Extraversion (r = 0.34, p <0.05), Conscientiousness (r = 0.20, p <0.05), dan Openness to Experience (r = 0.27, p <0.05) berhubungan secara signifikan dengan self-efficacy mahasiswa ketika melaksanakan mata kuliah praktikum. Temuan ini berimplikasi pada pemahaman kepribadian yang sangat penting untuk mendukung pengembangan profesional mahasiswa. Practical courses have different challenges from theoretical courses. Many factors are related to student self-efficacy when taking practical courses. This research is motivated by the phenomenon of several students who have difficulty following counselling practice courses. The focus of this study is to predict self-efficacy based on personality traits. Ten Items Personality Inventory (TIPI) and Self-Efficacy Learning Performance (SELP) were given to 103 students and analyzed using product moment correlation. The results showed that Extraversion (r = 0.34, p < 0.05), Conscientiousness (r = 0.20, p < 0.05), and Openness to Experience (r = 0.27, p < 0.05) which relates significantly to student self-efficacy when carrying out practical courses. These findings have implications for understanding personality which is essential for supporting the professional development of students.